RETRACTED ARTICLE: THE USE OF SCIENCE ENVIRONMENT TECHNOLOGY AND SOCIETY (SETS) LEARNING MODEL FOR ENHANCING THE CRITICAL THINKING SKILLS AND SCIENTIFIC ATTITUDES - Maimunah, Maimunah (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract This research purposed to determine the improvement of student’s scientific attitudes and critical thinking skills on the colloidal concept with implementation the learning model science environment technology and society (SETS). The method for this study is quasi-experimental with research design